On the pathway from projects to systematic change - Bašić, Sanela (Teorija in praksa, 2009)
The article discusses the transition of the welfare system in Bosnia and Herzegovina. The author begins by focusing on the main faces of the transition and pinpoints unique features of the Bosnian experience. It continues with a brief elaboration of the role of non-governmental organisations in providing social welfare during the socialist regime, war period and in the process of transition. Special attention is given to the new legislation enacted by the end of 1990, which provided the possibility to develop a plural model of welfare. The author presents the biggest achievements and challenges faced on the path to a more participative and empowering welfare system. The paper provides examples in order to support the claim that the NGO sector has played a crucial role in bringing about substantive changes in the way the welfare system is moving away from the classical welfarism of the pre-war period towards empowerment and participation during the transition.
Keywords: Država blaginje; Welfare state; Social policy; Socialna politika; Nevladne organizacije; Nongovernmental organizations; Transition; Tranzicija; Bosna in Hercegovina; Bosnia and Herzegovina